Influence of calcium hydroxide points on the quality of intracanal dressing filling (Journal of Applied Oral Science, 2006)
PURPOSE: The aim of this study was to evaluate, in vitro, the quality of calcium hydroxide [Ca(OH)2] paste filling (Ultracal, Ultradent) associated or not with Ca(OH)2-containing gutta-percha points (Calcium Hydroxide Plus PointsTM, Roeko) in curved root canals. MATERIAL AND METHODS: One hundred and twenty roots of extracted human teeth, randomly divided into three curvature ranges (mild - 0 to 14º; moderate - 15º to 29º; severe - >;30º) were used. After chemomechanical preparation, the roots were assigned to 4 groups (n=30), according to the technique of intracanal dressing placement: group 1 - Ca(OH)2 paste was applied with a lentulo spiral; group 2 - Ca(OH)2 paste was applied with a lentulo spiral and a Ca(OH)2 point was inserted into the canal; group 3 - Ca(OH)2 paste was applied with a NavitipTM tip (supplied with Ultracal system); group 4 - Ca(OH)2 paste was applied with a NavitipTM tip and a Ca(OH)2 point was inserted into the canal. The roots were cleared and the quality of apical third filling was assessed by a calibrated experienced examiner. The specimens were examined under stereomicroscopy and scored 1 to 4 (i.e., from inadequate to complete root canal filling). The results were analyzed statistically by ANOVA and Duncan's post hoc test at 5% significance level. RESULTS: There were no statistically significant differences (p>;0.05) among the curvature degrees in groups 1, 3 and 4. Severely curved roots in group 2 presented bordering significance (p=0.05). The groups that associated the use of Ca(OH)2 paste and points (2 and 4) showed better apical filling than the other groups, but this difference was statistically significant (p